Disaster insurance in developing Asia: An analysis of market-based schemes - Swenja Surminski; Architesh Panda; Peter John Lambert (Asian Development Bank (ADB), 2019)
In recent years, insurance against natural disasters has gained recognition as an important tool for climate risk management that could, if carefully implemented, help increase the resilience of those insured. In response, insurance solutions are increasingly tested and applied in many countries that have no prior experience with insurance or no existing market. This paper analyzes the status, types, and patterns of market-based disaster insurance schemes across emerging and developing countries in Asia. We provide a snapshot of the current use of insurance based on data from Grantham Research Institute on Climate Change and the Environment's Disaster Risk Transfer Scheme Database (2012-2018). Our analysis shows that although the use of insurance is expanding, there are many countries that still don't have any kind of cover available. Where insurance mechanisms exist, they often rely on subsidies or bundling strategies. Although a mix of insurance schemes covering risks for governments (sovereign); or at meso (risk aggregators, cooperatives); and micro level currently operate to address a wide variety of climate and disaster risks, without demand-side support, many markets are likely to collapse or, at the very least, experience far lower penetration rates. We conclude with a discussion of the role of these insurance schemes in increasing resilience, which raises important questions for designing new and measuring and evaluating existing insurance schemes.
Keywords: G22; G32; Q54; 330; Asia; climate change; disaster insurance; resilience